Change in motives among frequent cannabis-using adolescents: Predicting treatment outcomes. (1st October 2016) - Blevins, Claire E.; Banes, Kelsey E.; Stephens, Robert S.; Walker, Denise D.; Roffman, Roger A.
Highlights: Motives for cannabis use can predict problematic use and use-related problems. A MET/CBT intervention was associated with significant reductions in motives. Reductions in a subset of motives significantly predicted change in outcomes. Abstract: Background: Heavy cannabis use has been associated with negative outcomes, particularly among individuals who begin use in adolescence. Motives for cannabis use can predict frequency of use and negative use-related problems. The purpose of the current study was to assess change in motives following a motivational enhancement therapy (MET) and cognitive behavioral therapy (CBT) intervention for adolescent users and assess whether change in motives was associated with change in use and self-reported problems negative consequences. Methods: Participants (n = 252) were non-treatment seeking high school student cannabis users. All participants received two sessions of MET and had check-ins scheduled at 4, 7, and 10 months. Participants were randomized to either a motivational check-in condition or an assessment-only check-in. Participants in both conditions had the option of attending additional CBT sessions. Cannabis use frequency, negative consequences, and motives were assessed at baseline and at 6, 9, 12, and 15 month follow-ups. Results: There were significant reductions in motives for use following the intervention and reductions in a subset of motives significantly and uniquely predicted change in problematic outcomes beyond current cannabis use frequency. Change in motives was significantly higher among those who utilized the optional CBT sessions. Conclusions: This study demonstrates that motives can change over the course of treatment and that this change in motives is associated with reductions in use and problematic outcomes. Targeting specific motives in future interventions may improve treatment outcomes.